Composição do substrato sobre o desenvolvimento, qualidade e custo de produção de mudas de Eucalyptus grandis Hill ex Maiden × eucalyptus urophylla S. T. Blake - Simões, Danilo [UNESP]; da Silva, Richardson Barbosa Gomes [UNESP]; da Silva, Magali Ribeiro [UNESP] (My University, 2012)
The components used in the production of substrates influence directly the growth cycle, quality and consequently the cost of production of seedlings. In this experiment we studied the development, quality and cost of Eucalyptus grandis Hill ex Maiden × E. urophylla S. T. Blake, through sexual propagation using 12 compositions of substrate. The results showed that the pure substrates, with the exception of coconut fiber, did not present physical characteristics appropriate for the production from seedlings of eucalyptus in container, with the best results obtained for the substrates with a mixture 1:1 of carbonized rid of rice and coconut-fiber and a mixture 1:1 of vermiculite and coconut fiber, due to the best morphological characteristics and the possibility of reducing the production period which enables a reduction in the cost of final seedling.
Composition of the substrate on the development, quality and cost of production of seedlings of Eucalyptus grandis Hill ex Maiden × eucalyptus urophylla S. T. Blake
Keywords: Coconut-fiber; Nursery; Physical properties; Vermiculite